Geotechnical Engineering Unsaturated and Saturated Soils - Briaud, Jean-Louis (Wiley, 2023)
While there are many textbooks on the market that cover geotechnical engineering basics, Geotechnical Engineering is unique in that it is the only textbook available that is rooted within the three phase unsaturated soil mechanics framework. Written by world-renowned, award-winning geotechnical engineering expert Dr. Jean-Louis Briaud, this Second Edition offers the most comprehensive coverage of geotechnical engineering topics on the market, from theory to real-world application.From site investigation and geophysics to earthquake engineering and deep foundations, Geotechnical Engineering is an ideal resource for upper-level undergraduate and graduate courses, as well as practicing professionals in geotechnical engineering and soil mechanics.